Pemaknaan Hadis-Hadis Isbal oleh Kelompok Salafi Pondok Pesantren Tahfidz Al-Qur’an Harun As-Syafi’i, Yogyakarta: Analisis Teori Resepsi - Yeti Dahliana; Ahmad Nurrohim; Alfiyatul Azizah (Diroyah : Jurnal Studi Ilmu Hadis, 2021)
The figure of Prophet Muhammad is a guide and role model of the whole matters of life for the Muslims. It was starting from religious to domestic matters. Likewise, with the problem of clothing, the Prophet has been guided through his sunnah, written in the hadith. Today, some Muslims attempt to reviving the sunnah and embodying it in their life. The phenomenon of reviving the sunnah with jargon back to the Quran and Sunnah has seemed familiar to us. This paper tries to explore how the Salafi of Pondok Pesantren Tahfidz al-Qur’an Harun as-Syafi’i, Karangkajen, Yogyakarta recepties and embodies the isbal hadiths in their daily life. This research uses a qualitative descriptive method with a living hadith approach.  In this research, the Salafi has the high spirit of reviving and embodying every sunnah of the Prophet. Thus, the sunnah is not only mute text, but it becomes the living hadith (in this case is non-isbal clothes). The Salafi, understanding this hadith, was obliged to Muslims wearing non-isbal clothes. This manner reflects two models of reception, namely exegetical reception and functional reception